2004
DOI: 10.1200/jco.2004.03.087
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Therapy for Stage II Colon Cancer: A Systematic Review From the Cancer Care Ontario Program in Evidence-Based Care’s Gastrointestinal Cancer Disease Site Group

Abstract: There is preliminary evidence indicating that adjuvant therapy is associated with a disease-free survival benefit for patients with stage II colon cancer. These benefits are small and not necessarily associated with improved overall survival. Patients should be made aware of these results and encouraged to participate in active clinical trials. Additional investigation of newer therapies and more mature data from the presently available trials should be pursued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
195
1
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(205 citation statements)
references
References 44 publications
4
195
1
5
Order By: Relevance
“…[2][3][4][5][6] Currently, adjuvant chemotherapy is an accepted standard of care for patients with stage III colon cancer but is not recommended for the treatment of patients with stage II disease. 7 However, patients with high-risk, lymph node-negative disease, including those with pT4 tumors, may be considered for therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] Currently, adjuvant chemotherapy is an accepted standard of care for patients with stage III colon cancer but is not recommended for the treatment of patients with stage II disease. 7 However, patients with high-risk, lymph node-negative disease, including those with pT4 tumors, may be considered for therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a systematic review of 4187 patients from 37 trials and 11 meta-analyses was performed by the Cancer Care Ontario Program. 5 Their findings included a relative risk of 0.87 that indicated a survival benefit from chemotherapy. Although improved survival was demonstrated in those trials, differences in the length of survival did not reach statistical significance.…”
mentioning
confidence: 99%
“…although adjuvant chemotherapy provides a significant survival benefit in stage III patients, whether this treatment has any effect on patients with stage ii colon cancer remains controversial, since 20-30% of these patients eventually experience tumor relapses (2). adjuvant chemotherapy was shown to increase the survival of certain populations of stage ii patients (3). Furthermore, it was found that 60% of stage iii patients did not relapse, even when adjuvant chemotherapy was not used (4).…”
Section: Introductionmentioning
confidence: 99%
“…4 Adjuvant chemotherapy has been shown to increase survival in certain populations of Stage II patients. 5 Furthermore, almost 60% of Stage III patients do not relapse, even if adjuvant chemotherapy is not given. 6 Therefore, identification of highrisk Stage II and III colorectal cancer patients would be of great benefit in selecting appropriate candidates for standard or intense adjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%